Temporal autoregulation during human PU.1 locus SubTAD formation - Schuetzmann, Daniel; Walter, Carolin; Riel, Boet van; Kruse, Sabrina; König, Thorsten; Erdmann, Tabea; Tönges, Alexander; Bindels, Eric; Weilemann, Andre; Gebhard, Claudia; Wethmar, Klaus; Perrod, Chiara; et al. (Blood, 2018)
Visual Abstract - Download figureOpen in new tabDownload powerpoint - - Epigenetic control of gene expression occurs within discrete spatial chromosomal units called topologically associating domains (TADs), but the exact spatial requirements of most genes are unknown; this is of particular interest for genes involved in cancer. We therefore applied high-resolution chromosomal conformation capture sequencing to map the three-dimensional (3D) organization of the human locus encoding the key myeloid transcription factor PU.1 in healthy monocytes and acute myeloid leukemia (AML) cells. We identified a dynamic ∼75-kb unit (SubTAD) as the genomic region in which spatial interactions between PU.1 gene regulatory elements occur during myeloid differentiation and are interrupted in AML. Within this SubTAD, proper initiation of the spatial chromosomal interactions requires PU.1 autoregulation and recruitment of the chromatin-adaptor protein LDB1 (LIM domain-binding protein 1). However, once these spatial interactions have occurred, LDB1 stabilizes them independently of PU.1 autoregulation. Thus, our data support that PU.1 autoregulates its expression in a “hit-and-run” manner by initiating stable chromosomal loops that result in a transcriptionally active chromatin architecture.
Gesehen am 27.08.219